The relationships between 25-hydroxyvitamin D and echocardiographic parameters in female basketball players - Radovanovic, D.; Stoickov, V.; Pechanova, O.; Scanlan, A. T.; Jakovljevic, V.; Stojanovic, E. (Clinical Journal of Sport Medicine, 2022)
Objective: This study was undertaken to (1) describe the cardiac structure and function and (2) to quantify the relationships between 25-hydroxyvitamin D [25(OH)D] and echocardiographic parameters in female basketball players.